2021
DOI: 10.54991/jop.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges in understanding Asian palaeogeography and monsoon evolution from the perspective of the plant fossil record

Abstract: Land surface elevation, climate and vegetation are intrinsically linked at a range of spatial and temporal scales. In the case of Asia, complex relief hosts some of the richest biodiversity on our planet and is dominated by a system of monsoons, the features of which are determined in large part by topography and land surface characteristics, including vegetation. Such regions have not only acted as an incubator for evolving species but also as refugia during periods of environmental crisis. The exceptional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…After distinguishing this definition, the latest studies suggest that the Asian monsoon was disassociated from the ITCZ and extended into Yunnan 36 or 41 Ma (Fang et al, 2021;Zheng et al, 2022), affecting the Nangqian Basin after 35 Ma (Fang et al, 2022), and that the modern-like Asian monsoon pattern formed in the Late Oligocene-Early Miocene (e.g., Wu et al, 2022). the growth of the Tibetan Plateau (e.g., An et al, 2001An et al, , 2006Boos & Kuang, 2010;Farnsworth et al, 2019;Guo et al, 2002;Liu & Yin, 2002;Liu et al, 2017;Manabe & Terpstra, 1974;Molnar et al, 1993;Prell & Kutzbach, 1992;Spicer & Farnsworth, 2021;Wu et al, 2012;Zhang et al, 2007), orbital variation (Tardif et al, 2021), atmospheric CO 2 (Licht et al, 2014;Tardif et al, 2023), the ice-sheet state, and oceanic gate-ways (Thompson et al, 2021), all of which still impact the Asian monsoon. The Indian summer monsoon is slightly different, with simulations showing contribution ratios of 39% for orography, 25% for precession, 21% for atmospheric CO 2 , 5% for the ice-sheet state, 5% for the oceanic gateways (Thompson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After distinguishing this definition, the latest studies suggest that the Asian monsoon was disassociated from the ITCZ and extended into Yunnan 36 or 41 Ma (Fang et al, 2021;Zheng et al, 2022), affecting the Nangqian Basin after 35 Ma (Fang et al, 2022), and that the modern-like Asian monsoon pattern formed in the Late Oligocene-Early Miocene (e.g., Wu et al, 2022). the growth of the Tibetan Plateau (e.g., An et al, 2001An et al, , 2006Boos & Kuang, 2010;Farnsworth et al, 2019;Guo et al, 2002;Liu & Yin, 2002;Liu et al, 2017;Manabe & Terpstra, 1974;Molnar et al, 1993;Prell & Kutzbach, 1992;Spicer & Farnsworth, 2021;Wu et al, 2012;Zhang et al, 2007), orbital variation (Tardif et al, 2021), atmospheric CO 2 (Licht et al, 2014;Tardif et al, 2023), the ice-sheet state, and oceanic gate-ways (Thompson et al, 2021), all of which still impact the Asian monsoon. The Indian summer monsoon is slightly different, with simulations showing contribution ratios of 39% for orography, 25% for precession, 21% for atmospheric CO 2 , 5% for the ice-sheet state, 5% for the oceanic gateways (Thompson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that the formation and evolution of the Asian summer monsoon during the Cenozoic were closely related to changes in the land–sea distribution (including the retreat of the Paratethys Sea), the growth of the Tibetan Plateau (e.g., An, 2014; An et al., 2001, 2006; Boos & Kuang, 2010; Farnsworth et al., 2019; Guo et al., 2002; S.‐F. Li et al., 2021; Liu & Yin, 2002; Liu et al., 2017; Manabe & Terpstra, 1974; Molnar et al., 1993; Prell & Kutzbach, 1992; Spicer & Farnsworth, 2021; Wu et al., 2012; Zhang et al., 2007), orbital variation (Tardif et al., 2021), atmospheric CO 2 (Licht et al., 2014; Tardif et al., 2023), the ice‐sheet state, and oceanic gate‐ways (Thompson et al., 2021), all of which still impact the Asian monsoon. The Indian summer monsoon is slightly different, with simulations showing contribution ratios of 39% for orography, 25% for precession, 21% for atmospheric CO 2 , 5% for the ice‐sheet state, 5% for the oceanic gateways (Thompson et al., 2021).…”
Section: Introductionmentioning
confidence: 99%